2015
DOI: 10.1038/tp.2015.160
|View full text |Cite
|
Sign up to set email alerts
|

Effective emotion regulation strategies improve fMRI and ECG markers of psychopathology in panic disorder: implications for psychological treatment action

Abstract: Impairments in emotion regulation are thought to have a key role in the pathogenesis of anxiety disorders, but the neurobiological underpinnings contributing to vulnerability remain poorly understood. It has been a long-held view that exaggerated fear is linked to hyperresponsivity of limbic brain areas and impaired recruitment of prefrontal control. However, increasing evidence suggests that prefrontal–cortical networks are hyperactive during threat processing in anxiety disorders. This study directly explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 76 publications
(108 reference statements)
6
39
0
Order By: Relevance
“…In some studies this pattern extended into the premotor cortex/SMA as well (Table 2). However, unlike individuals with mood disorders, those with anxiety disorders did not show enhanced amygdala responses during downregulation (both negative and positive) (Table 2, 3), even when the amygdala was included in a ROI analysis without correction for multiple comparisons (New et al, 2009; Rabinak et al, 2014; Reinecke et al, 2015). In fact, only one study reported increased activation levels during downregulation in any region, specifically showing that both the caudate and the dlPFC activity were increased during downregulation of negative emotion in patients with anxiety disorders as compared to healthy controls (Goldin et al, 2009a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies this pattern extended into the premotor cortex/SMA as well (Table 2). However, unlike individuals with mood disorders, those with anxiety disorders did not show enhanced amygdala responses during downregulation (both negative and positive) (Table 2, 3), even when the amygdala was included in a ROI analysis without correction for multiple comparisons (New et al, 2009; Rabinak et al, 2014; Reinecke et al, 2015). In fact, only one study reported increased activation levels during downregulation in any region, specifically showing that both the caudate and the dlPFC activity were increased during downregulation of negative emotion in patients with anxiety disorders as compared to healthy controls (Goldin et al, 2009a).…”
Section: Resultsmentioning
confidence: 99%
“…Lang et al, 2012; Manber-Ball, Ramsawh, Campbell-Sills, Paulus, & Stein, 2013; Marissen, Meuleman, & Franken, 2010; Morris, Sparks, Mitchell, Weickert, & Green, 2012; New et al, 2009; Paul, Simon, Endrass, & Kathmann, 2015; Rabinak et al, 2014; Reinecke et al, 2015; Reinecke, Thilo, Filippini, Croft, & Harmer, 2014; Schulze et al, 2011; Smoski, Keng, Schiller, Minkel, & Dichter, 2013; Townsend et al, 2013; van der Meer et al, 2014; Wang et al, 2014; Woodward et al, 2015; Wu et al, 2015; Ziv, Goldin, Jazaieri, Hahn, & Gross, 2013). …”
Section: Figurementioning
confidence: 99%
“…Of those, n = 68 entered our quantitative synthesis (for an overview see Table 3). The remaining 10 studies (Delgado et al, 2008;Driscoll et al, 2009;Jamieson et al, 2012Jamieson et al, , 2013Peters et al, 2014;Baur et al, 2015;Reinecke et al, 2015;Peters and Jamieson, 2016;Zaehringer et al, 2018;Kotwas et al, 2019) were not considered, as a meta-analysis on the respective combination of emotion regulation strategy and psychophysiological measure was not possible because the number of studies was too small. See Figure 1 for a PRISMA flowchart depiction of the screening and selection of studies.…”
Section: Inclusion/exclusion Criteriamentioning
confidence: 99%
“…Patients performed an emotion regulation task on the day after treatment during 3T MRI (14). IAPS images showing negatively valenced panic-related scenes (e.g.…”
Section: Secondary Outcomes I) Mrimentioning
confidence: 99%